2014
DOI: 10.1111/jvs.12261
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of lake macrophyte communities and species richness at regional scale

Abstract: Questions Are community composition and species richness of aquatic macrophytes determined primarily by local (habitat heterogeneity and water quality) or regional (climate) patterns at regional scale? Do two macrophyte functional groups (i.e. emergent and submerged macrophytes) respond similarly to local and regional patterns? Are lake macrophytes and explanatory variables geographically structured? Location The US state of Minnesota. Methods The community composition and species richness of aquatic flora was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
73
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 64 publications
(166 reference statements)
13
73
5
Order By: Relevance
“…However, our study lends further support to this evidence and highlights the need for further investigations. Indeed, the majority of both earlier and more recent works on this topic focused predominantly, or even exclusively, on water conditions when analyzing macrophyte patterns, neglecting the potential role of sediment (Kolada, 2010;Alahuhta, 2015;Lukács et al, 2015;Pulido et al, 2015). Furthermore, previous investigations that did analyze the depth distribution of macrophytes often included depth among the environmental determinants tested, thereby limiting the analytical potential of the studies and references therein), or used data mainly from shallow ecosystems (Søndergaard et al, 2013).…”
Section: Environmental Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study lends further support to this evidence and highlights the need for further investigations. Indeed, the majority of both earlier and more recent works on this topic focused predominantly, or even exclusively, on water conditions when analyzing macrophyte patterns, neglecting the potential role of sediment (Kolada, 2010;Alahuhta, 2015;Lukács et al, 2015;Pulido et al, 2015). Furthermore, previous investigations that did analyze the depth distribution of macrophytes often included depth among the environmental determinants tested, thereby limiting the analytical potential of the studies and references therein), or used data mainly from shallow ecosystems (Søndergaard et al, 2013).…”
Section: Environmental Determinantsmentioning
confidence: 99%
“…The majority of recent works on the relationship between macrophytes and the environment, which have generally been performed on very large datasets and have thus been characterized by a very marked variance, did not detect any degree of randomness in macrophyte cooccurrence before the role of expected driving factors was tested (Kolada, 2010;Alahuhta, 2015). Our findings in-N o n -c o m m e r c i a l u s e o n l y dicate that not testing these factors may result in a misinterpretation of the determinants of macrophyte co-occurrence patterns as well as of their edaphic determinants.…”
Section: Implications For Ecological Study Biomonitoring and Lake CLmentioning
confidence: 99%
“…To overcome some of these difficulties in investigating freshwater biodiversity patterns, multiple regions should be investigated simultaneously using the same study approach and identical statistical methods to maintain reliable comparability among the study results Heino, Melo, Siqueira, et al, 2015;Tonkin et al, 2016 Alahuhta, Virtala, et al (2017) showed, using almost identical data to our present study, that land use significantly influenced average water quality niche breadths of lake macrophytes in Finland, Sweden and Wisconsin. The study lakes were randomly selected from a larger database of lakes in Finland and Minnesota (Alahuhta, 2015; to maintain comparability with the lower numbers of study lakes from Sweden and Wisconsin. The number of studied lakes was 50 in Sweden and Wisconsin and 60 in Finland and Minnesota.…”
mentioning
confidence: 99%
“…The study lakes were randomly selected from a larger database of lakes in Finland and Minnesota (Alahuhta, 2015; to maintain comparability with the lower numbers of study lakes from Sweden and Wisconsin. Macrophyte survey methods are described in detail for Finland in , for Sweden in Naturv ardsverket (2010), for Minnesota in Alahuhta (2015) and for Wisconsin in Sass et al (2010). Surveys were executed in all the study areas during the growing season Table 1).…”
mentioning
confidence: 99%
“…However, this study referred to changes in vegetation patterns in the total covered area, but not in relation to lake area. On the other hand, an increased share of helophytes, typically, is associated with a rise in water trophy in opposition to hydrophytes [8,32].…”
Section: Relationship Between Macrophyte Forms In Overgrowing Lakesmentioning
confidence: 99%